2014
DOI: 10.1051/0004-6361/201321567
|View full text |Cite
|
Sign up to set email alerts
|

Disk emission and atmospheric absorption lines in black hole candidate 4U 1630-472

Abstract: Context. We analyzed Suzaku data of the black hole candidate 4U 1630-472 when it was in the high/soft state. The source, known for X-ray outbursts and for absorption dips, has an X-ray continuum spectrum that is interpreted correctly as emission from an accretion disk. Additionally, two absorption lines from He and H-like iron have been clearly detected in the high-resolution data from 4U 1630-472. Aims. We show that the continuum X-ray spectrum of 4U 1630-472 with iron absorption lines can be satisfactorily m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 31 publications
5
16
0
Order By: Relevance
“…Compared to the parameters in Kubota et al (2007), Różańska et al (2014) and Díaz Trigo et al (2014), we find a higher value of N H than theirs and the temperature of the disc is higher than that of Kubota et al (2007). The energy of the absorption lines and edges are consistent with those of Fe xxv Heα (6.70 keV), Fe xxvi Lyα (6.97 keV), Ni xxviii Lyα (8.09 keV) or Fe xxv Lyβ (7.88 keV), Fe xxvi Lyβ (8.25 keV), Fe xxv K-edge (8.83 keV) and Fe xxvi K-edge (9.28 keV), similar to the identification in Díaz Trigo et al (2014).…”
Section: Fits To the Burst-and Timing-mode Observations Using The Oldmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the parameters in Kubota et al (2007), Różańska et al (2014) and Díaz Trigo et al (2014), we find a higher value of N H than theirs and the temperature of the disc is higher than that of Kubota et al (2007). The energy of the absorption lines and edges are consistent with those of Fe xxv Heα (6.70 keV), Fe xxvi Lyα (6.97 keV), Ni xxviii Lyα (8.09 keV) or Fe xxv Lyβ (7.88 keV), Fe xxvi Lyβ (8.25 keV), Fe xxv K-edge (8.83 keV) and Fe xxvi K-edge (9.28 keV), similar to the identification in Díaz Trigo et al (2014).…”
Section: Fits To the Burst-and Timing-mode Observations Using The Oldmentioning
confidence: 99%
“…Absorption lines due to highly ionised material have been observed in the spectrum of 4U 1630−47 (Kubota et al 2007;Różańska et al 2014;Díaz Trigo et al 2014;Miller et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal pressure consists of the heating of the gas by the central X-ray source, producing an outflow at large distances from the central object, when the thermal velocity is larger than the local escape velocity (Begelman et al 1983;Woods et al 1996;Netzer 2006; Higginbottom E-mail: egatuzzs@eso.org & Proga 2015;Higginbottom et al 2017). Radiative pressure can be produced by electrons scattering, at near-or super-Eddington luminosities, or lines (Różańska et al 2014;Hashizume et al 2015;Shidatsu et al 2016). However, it has been shown that, for BH LMXBs, radiation pressure cannot launch an outflow due to the low number of soft X-ray and UV lines (Proga & Kallman 2002).…”
Section: Introductionmentioning
confidence: 99%
“…From the observational point of view, thermal winds have been favored by a majority of observations (Kubota et al 2007;Neilsen & Homan 2012;Różańska et al 2014;Díaz Trigo & Boirin 2016;Allen et al 2018;Done et al 2018;Tomaru et al 2018) although radiation pressure due to electrons (Kotani et al 2000;Kubota et al 2007;Neilsen & Lee 2009a;Díaz Trigo et al 2014;Różańska et al 2014;Miller et al 2016b;Shidatsu et al 2016) and magnetic forces (Miller et al 2006a(Miller et al , 2008Luketic et al 2010;King et al 2014;Miller et al 2006aMiller et al , 2016aFukumura et al 2017;Tetarenko et al 2018) have also been invoked to explain a handful of cases.…”
Section: Introductionmentioning
confidence: 99%